The Importance of Kyai Charismatic Leadership in the Formation of Akhlakul Karimah - Rahayuningsih, Sri; Setiawan, Andi; Warisno, Andi; Andari, An An; Anshori, M Afif (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2023)
The goal of this research is to examine the role of charismatic kyai leadership in the moral development of students at Al Ishlah Islamic Boarding School. To investigate what factors, help and hinder the charismatic kyai's leadership in the moral formation of students at Al Ishlah Islamic Boarding School. This is a descriptive qualitative study. Data is gathered through interviews, observations, and documentation. Analysis data were done through data reduction, data presentation, and drawing conclusions. Based on the findings, it can be concluded that the kiai's role as a boarding school caretaker, example, parents, leader, and motivator. Characters formed include students who care about the environment, discipline, responsibility, independence, religion, and hard work. The existence of good management performance, the involvement of the Islamic Boarding School family, and the support of the community and government in the Islamic Boarding School are all supporting factors. Inhibiting factors include a lack of belonging to Islamic boarding schools' facilities and infrastructure, a lack of parental understanding of Islamic boarding school regulations, and the influence of children outside the boarding school.